A Small Interfering RNA Cocktail Targeting the Nucleoprotein and Large Protein Genes Suppresses Borna Disease Virus Infection - Teng, Da; Obika, Shunsuke; Ueda, Keiji; Honda, Tomoyuki (Frontiers in Microbiology, 2019)
Recently, Borna disease virus (BoDV-1)-related fatal encephalitis human cases have been reported, which highlights the potential of BoDV-1 to cause fatal human diseases. To protect the infected brain from lethal damage, it is critical to control BoDV-1 as quickly as possible. At present, antivirals against BoDV-1 are limited, and therefore, novel types of antivirals are needed. Here, we developed a novel treatment using small interfering RNAs (siRNAs) against BoDV-1. We screened several siRNAs targeting the viral N, M, and L genes for BoDV-1-reducing activity. Among the screened candidates, we chose two siRNAs that efficiently decreased the BoDV-1 load in persistently BoDV-1-infected cells to prepare a siRNA cocktail (TD-Borna) for BoDV-1 treatment. TD-Borna successfully reduced the BoDV-1 load without enhancing the risk of emergence of escape mutants. The combination of TD-Borna and T-705, a previously reported antiviral agent against bornaviruses, decreased the BoDV-1 load more efficiently than TD-Borna or T-705 alone. Furthermore, TD-Borna efficiently decreased the BoDV-1 load in BoDV-1-infected neuron-derived cells, in which T-705 did not decrease the viral load. Overall, we developed a novel antiviral candidate against BoDV-1, TD-Borna, that can be used in combination with T-705 and is effective against BoDV-1 in neuron-derived cells, in which T-705 is less effective. Considering that BoDV-1 is highly neurotropic, TD-Borna can offer a promising option to improve the outcome of BoDV-1 infection.